Validity of a new stabilometric force platform for postural balance evaluation. DOI: 10.5007/1980-0037.2011v13n5p367 - Philippe Kauffmann; Noé Gomes Borges Junior; Susana Cristina Domenech; Marcelo Diederichs Wentz; Daniela Junckes da Silva Mattos; Lucas Borges; Jonathan Ache Dias (Universidade Federal de Santa Catarina, 2011)
The objective of this study was to validate a new stabilometric force platform (SFP). For this, three steps have been established: a) to determine the force threshold to reach an acceptable level of accuracy of the centre of pressure (CoP) measurement by the application of single point load; b) to determine the accuracy of the CoP measurement in the application of distributed load simulating the human feet; c) to verify the concurrent validity of the SFP by comparing it with a commercial force platform (FP). The tests performed in steps "a" and "b" were conducted by applying loads on the SFP using a universal testing machine. In the application of single point load, the mean force threshold presentedby the SFP was 315.6 ± 140.5 N. The CoP measurement error in the points near the centre of the SFP was 1.04 ± 0.80 mm in medial-lateral (ML) and 1.31 ± 0.99 mm in anteriorposterior (AP) direction. In the points near the edges of the plate, the error was 2.03 ± 0.91mm (ML) and 1.54 ± 0.96 mm (AP). In the test with distributed loads, errors of less than 1 mm were found. Additionally, no differences were found in the CoP parameters between SFP and the FP. The CoP measurement signal presented high correlation between bothequipments in AP (r = 0.997 ± 0.001) and ML (r = 0.988 ± 0.003) directions. These findings suggest that the SFP can be used in scientific investigations of balance in quiet standing.